2022
DOI: 10.3389/fpubh.2022.921243
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccination coverage of patients with type 2 diabetes mellitus: Challenging issues from an outpatient secondary care setting in Greece

Abstract: BackgroundIncreased morbidity/mortality due to vaccine preventable diseases (VPD) is encountered in type 2 diabetes (T2D) people. Aim of this study was to assess their vaccination coverage and describe trends possibly affecting compliance.MethodsInformation on vaccination coverage was retrieved from either documents or interview provided by patients, and/or their vaccination record card at a specialized outpatient diabetes center. The selection of the patients was arbitrary.ResultsAn increasing vaccination rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Although this rate is low, it is still higher than the rate of 4.5% in Riyadh and 18% in the whole Kingdom among patients with a history of HZ [ 4 , 21 ]. Our findings are consistent with the coverage rate in Greece, which was reported as 26.3% for the HZ vaccine among individuals with diabetes aged 60 years and older [ 22 ]. A wide range of variations have been noted in HZ vaccination coverage in different countries.…”
Section: Discussionsupporting
confidence: 92%
“…Although this rate is low, it is still higher than the rate of 4.5% in Riyadh and 18% in the whole Kingdom among patients with a history of HZ [ 4 , 21 ]. Our findings are consistent with the coverage rate in Greece, which was reported as 26.3% for the HZ vaccine among individuals with diabetes aged 60 years and older [ 22 ]. A wide range of variations have been noted in HZ vaccination coverage in different countries.…”
Section: Discussionsupporting
confidence: 92%
“…Thanks to the dedicated service we managed to create for these patients at risk, we have achieved a level of adherence to vaccinations after proper counseling in over 90% of cases; this rate, for the same vaccines performed, is above the rates of adherence to vaccines reported globally for cases of patients with ADs [20,21] or with other types of diseases at risk (diabetics [22,23], chronic lung diseases [24], splenectomized [25] patients).…”
Section: Discussionmentioning
confidence: 80%
“…The International Diabetes Federation (IDF) has observed that type 2 diabetes (T2D) is a rapidly growing global health concern that has reached epidemic proportions. Additionally, the number of new cases of T2D is projected to affect one out of every ten individuals worldwide by 2035 [10,11].Furthermore, according to the World Health Organization (WHO), Saudi Arabia ranks as the second-highest country in terms of diabetes prevalence in the Middle East and the seventh highest in the world [12]. A twenty-year audit study of herpes zoster (HZ) in the Asia-Pacific region identified immune senescence and immunosuppression as the principal risk factors for HZ [13].…”
Section: Resultsmentioning
confidence: 99%